Improving Performance of Heifer Buffalos Fed with Urea-treated Rice Straw Ensiled with Cassava Pulp Supplemented with Concentrates - Bata, Muhamad; Rahayu, Sri; Marung, Nova; Sumaryadi, Mas Yedi (ANIMAL PRODUCTION, 2020)
The objectives of this research were the optimalization of production and reproduction of buffalo heifers through improving feed quality based on rice straw. Twelve heifer buffaloes with body weight of 243 – 350 kg were kept in individual cages and grouped to four. Each groups were randomized to receive three treatments of A, B and C according to Randomized Completely Block Design (RCBD). A was buffalo fed only rice straw. B was buffalo fed rice straw supplemented with concentrate with a dry matter ratio of 70:30. C was similar to B but the rice straw was ammoniated using urea of 4% ensiled with 8% of cassava pulp. In-Vitro test was conducted to measure rumen fermentation product. The results showed the highest of DM and OM digestibility was achieved at C treatment, while the lowest was found at A treatment. Rumen fermentation produsts and its efficiency were the highest in C treatment. In-vivo result showed that ADG of C was higher than that of B and A. Reproductive performance characterized by frequency oestrus for 123 days were an average of 2.5, 2.8 and 4.5 times for A, B and C, respectively. The highest blood metabolite of glucose, urea and erytrocyt was found at C but the leucocyt was lowest compared to A and B. Urea treated rice straw ensiled with cassava pulp and supplemented with concentrate can improve production and reproduction performance of heifer buffaloes.